Best Evidence Medical and Health Professional Education (BEME) collaboration: A moving spotlight. (2nd January 2016) - Gordon, Morris; Patricio, Madalena Folque
Abstract: Early this year, a Massachusetts Institute of Technology professor of philosophy presented a new theory of time that caught our interest. One of the key concepts that Professor Skow presented is the "moving spotlight" theory. As Skow asserts, the experiences had a year ago or 10 years ago are still just as real, they're just "inaccessible" because they are now in a different part of spacetime. This was felt to be an elegant notion to inform this 'spotlight' piece on BEME (www.bemecollaboration.org ).